ODOUR STUDY WITH QUALITATIVE AND QUANTITATIVE RESEARCH METHODS IN VARIOUS DISTRICTS OF RIGA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Different emission sources of odours become increasingly important environmental problem which may have a negative impact on human health and quality of life. Human odour perception may be subjective, however on odour perception threshold is considered to be the odorant concentration where at least half of odour assessor’s group members confirm the existence of odour, and then it is 1 OUE /m3. Nowadays more and more advanced technologies are used to measure odour concentration. Olfactometer Scentroid SM100 allows users to accurately quantify ambient odour concentration in field. Also this equipment allows to collect source samples and analyze odour in a laboratory. Odour study in 2016 and 2017 with field olfactometer Scentroid SM100 and gas analyzer Gasmet DX-4030 in districts of Riga indicates that the highest concentrations of odour are in Bolderaja, Sarkandaugava, Kundzinsala, Mangalsala, Milgravis and Vecmilgravis. Study indicates that the highest odour concentrations, especially among producing companies can reach up to 6-7 odour units (OUE/m3), however gas analyzer Gasmet DX-4030 indicates oil products or carbon dioxide.